KONTRIBUSI KOMPETENSI SDM, KAPASITAS SDM DAN PEMANFAATAN TEKNOLOGI INFORMASI TERHADAP KETERANDALAN PELAPORAN KEUANGAN DAERAH (Studi pada BKAD Kota Malang) - Selynia Nurur Rohmah; M. Cholid Mawardi; Hariri Hariri (e_Jurnal Ilmiah Riset Akuntansi, 2022)
This study aims to determine the effect of human resource competence, human resource capacity and the use of information technology on the reliability of local government financial reports at BKAD Malang City. The population in this study were BKAD employees/staff of Malang City. Meanwhile, the sample from this study that was in accordance with the criteria determined by the researcher was the head of the agency, the secretary of the agency, the budget, treasury and accounting staff, totaling 33 respondents. The analytical method used was Multiple Linear Regression analysis. After data analysis was carried out, the results of the study using the t test and F test stated that there were the influence of Human Resource Competence, human resource capacity and the use of information technology on the reliability of local government financial reports at the BKAD Malang City will increase too.Keywords: Human resource competence, Human resource capacity, Information technology, The reliability of financial report.